The Management of socio – emotional skills in Spanish Language and Literature - Marcos Sánchez, Rafael; Díez González, María del Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this research we tested a relational model between six social-emotional skills, perception and academic results in Spanish Language and Literature on 640 students from fourth to sixth grade of Primary School. The results obtained in the analysis show significance between the perception and the actual result obtained in Language and the skills of emotional awareness and control, social-emotional skills, cooperation and help during work, life skills and subjective well-being as an improvement in the quality of life and as a motivational power in academic performance in Spanish Language and Literature.